The Effects of Coupling Agents on the Properties of Polyimide/Nano-Al2O3 Three-Layer Hybrid Films. (16th September 2010) - Liu, Lizhu; Weng, Ling; Song, Yuxia; Gao, Lin; Lei, Qingquan
Abstract : PI/nano-Al2 O3 hybrid films were prepared by ultrasonic-mechanical method. Before addition, nano-Al2 O3 particles were firstly modified with different coupling agents. The micromorphology, thermal stability, mechanical properties, and electric breakdown strength of hybrid films were characterized and investigated. Results indicated that nano-Al2 O3 particles were homogeneously dispersed in the PI matrix by the addition of coupling agents. The thermal stability and mechanical properties of PI/nano-Al2 O3 composite films with KH550 were the best. The tensile strength and elongation at break of PI composite film were 119.1 MPa and 19.1%, which were 14.2% and 78.5% higher than unmodified PI composite film, respectively.